Effect of sex on the gut microbiota characteristics of passerine migratory birds - Yan, Rongfei; Lu, Meixia; Zhang, Lishi; Yao, Jiyuan; Li, Shi; Jiang, Yunlei (Frontiers in Microbiology, 2022)
The gut microbiota, considered the "invisible organ" in the host animal, has been extensively studied recently. However, knowledge about the gut microbiota characteristics of passerine migratory birds during migration is limited. This study investigated the gut microbiota characteristics of three dominant migratory bird species (namely orange-flanked bluetail Tarsiger cyanurus, yellow-throated bunting Emberiza elegans, and black-faced bunting Emberiza spodocephala) in the same niche during spring migration and whether they were bird sex-specific. The compositions of gut microbiota species in these three migratory bird species and their male and female individuals were found to be similar. The main bacterial phyla were Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidetes, and the main genera were Lactobacillus, Acinetobacter, Rickettsiella, and Mycobacterium; however, their relative abundance was different. Moreover, some potential pathogens and beneficial bacteria were found in all the three bird species. Alpha diversity analysis showed that in T. cyanurus, the richness and diversity of the gut microbiota were higher in male individuals than in female individuals, while the opposite was true for E. elegans and E. spodocephala. The alpha diversity analysis showed significant differences between male and female individuals of E. elegans (p < 0.05). The beta diversity analysis also revealed that the gut microbial community structure differed significantly between the male and female individuals of the three migratory bird species.